Cyclic variations in incubation conditions induce adaptive responses to later heat exposure in chickens: a review. (14th August 2014) - Loyau, T.; Bedrani, L.; Berri, C.; Métayer-Coustard, S.; Praud, C.; Coustham, V.; Mignon-Grasteau, S.; Duclos, M. J.; Tesseraud, S.; Rideau, N.; Hennequet-Antier, C.; Everaert, N.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Selection programs have enabled broiler chickens to gain muscle mass without similar enlargement of the cardiovascular and respiratory systems that are essential for thermoregulatory efficiency. Meat-type chickens cope with high ambient temperature by reducing feed intake and growth during chronic and moderate heat exposure. In case of acute heat exposure, a dramatic increase in morbidity and mortality can occur. In order to alleviate heat stress in the long term, research has recently focused on early thermal manipulation. Aimed at stimulation of long-term thermotolerance, the thermal manipulation of embryos is a method based on fine tuning of incubation conditions, taking into account the level and duration of increases in temperature and relative humidity during a critical period of embryogenesis. The consequences of thermal manipulation on the performance and meat quality of broiler chickens have been explored to ensure the potential application of this strategy. The physiological basis of the method is the induction of epigenetic and metabolic mechanisms that control body temperature in the long term. Early thermal manipulation can enhance poultry resistance to environmental changes without much effect on growth performance. This review presents the main strategies of early heat exposure and the physiological concepts on which these methods were based. The cellular mechanisms potentially underlying the adaptive response are discussed as well as the potential interest of thermal manipulation of embryos for poultry production.